2020
DOI: 10.1055/a-1067-4411
|View full text |Cite
|
Sign up to set email alerts
|

EDGE in Roux-en-Y gastric bypass: How does it compare to laparoscopy-assisted and balloon enteroscopy ERCP: a systematic review and meta-analysis

Abstract: Background and study aims Endoscopic ultrasound-directed transgastric ERCP (EDGE) is a new endoscopic procedure to perform ERCP in Roux-en-y gastric bypass (RYGB) patients. The aim of this study was to conduct a systematic review and meta-analysis to evaluate technical success, clinical success and adverse effects of EDGE and compare it to laparoscopic ERCP (LA-ERCP) and balloon ERCP (BE-ERCP). Patients and methods We conducted a comprehensive search of several databases and conference proceedings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 55 publications
3
57
1
Order By: Relevance
“…2. A recent meta-analysis comparing EDGE with E-ERCP and LA-ERCP concluded that the technical and clinical success of EDGE is superior to E-ERCP and comparable to LA-ERCP [13]. Our study provides further comprehensive comparison of outcomes data at a single academic center, thereby allowing gastroenterologists to make educated decisions along with their patients regarding the choice of procedure.…”
Section: E880mentioning
confidence: 87%
“…2. A recent meta-analysis comparing EDGE with E-ERCP and LA-ERCP concluded that the technical and clinical success of EDGE is superior to E-ERCP and comparable to LA-ERCP [13]. Our study provides further comprehensive comparison of outcomes data at a single academic center, thereby allowing gastroenterologists to make educated decisions along with their patients regarding the choice of procedure.…”
Section: E880mentioning
confidence: 87%
“…Methodspecific AEs were minimal in this study, but numbers were too low for adequate comparison. The relative safety of E-ERCP suggested by a recent meta-analysis probably still holds true [4].…”
mentioning
confidence: 99%
“…Naturally, the three methods are alternatives that need comparative analysis. A recent meta-analysis addressed the issue [4], and concluded that the technical and clinical success of EDGE is better than that of E-ERCP and comparable to that of LA-ERCP, with adverse events (AEs) similar to that of the laparoscopic approach. At the moment, however, available data are all based on retrospective case series, where direct comparisons remain difficult.…”
mentioning
confidence: 99%
“…With advanced application of LAMS, we described a novel case of an EUS-directed transgastric ERCP procedure in a patient with RYGB anatomy in conjunction with a benign enteric stricture, which was performed through a dual transluminal conduit comprised of gastrogastrostomy and duodenal LAMS (▶ Video 1). This highly effective approach should be considered in clinical circumstances where balloon enteroscopy-assisted ERCP is technically challenging and when laparoscopy-assisted ERCP is not feasible [2,3].…”
mentioning
confidence: 99%